Comparison of Efficacy and Safety Outcomes of Different Doses Schedules of Thalidomide for Treating Moderate-to-Severe β-Thalassemia Patients - Yang WJ; Shi LD; Liang Y; Liang LM; Zhang H; Wang L; Zhou Q (Dove Medical Press, 2024)
Wei-Jia Yang,1,* Lian-dong Shi,2,* Ye Liang,3,* Li-ming Liang,4,* Hao Zhang,5 Li Wang,2 Qian Zhou1 1Department of Eugenics and Genetics, Guilin People's Hospital, Guilin, Guangxi Zhuang Autonomous Region, 541002, People's Republic of China; 2Department of Ultrasound, Guilin People's Hospital, Guilin, Guangxi Zhuang Autonomous Region, 541002, People's Republic of China; 3Department of Cardiology, The People's Hospital of Guangxi Zhuang Autonomous Region, and Institute of Cardiovascular Diseases, Guangxi Academy of Medical Sciences, Nanning, 530000, People's Republic of China; 4Department of Genetic Metabolism Center Laboratory, Guilin Women and Children's Hospital, Guilin, Guangxi Zhuang Autonomous Region, 541001, People's Republic of China; 5Department of Pharmacy, Guilin People's Hospital, Guilin, Guangxi Zhuang Autonomous Region, 541002, People's Republic of China*These authors contributed equally to this workCorrespondence: Wei-Jia Yang, Department of Eugenics and Genetics, Guilin People's Hospital, No. 12 of Wenming Road, Xiangshan District, Guilin, Guangxi Zhuang Autonomous Region, 541002, People's Republic of China, Tel +86 18977300052, Fax +86 07732881579, Email weijiayangywj@126.comObjective: In this study, we evaluated the effectiveness and safety of thalidomide by clinically observing 48 individuals with β-thalassemia who have been administered thalidomide in small and medium doses over a period of two years.Methods: Thalidomide's efficacy was gauged by tracking hemoglobin (Hb) level alterations post its administration. Liver and kidney function impact was measured through tests for alanine aminotransferase, aspartate aminotransferase, blood urea nitrogen, and creatinine. Hemolysis effects were assessed via total bilirubin and indirect bilirubin level measurements. Thrombosis detection was performed using ultrasound examinations of deep vein vessels in the upper and lower extremities. Any adverse effects of thalidomide were recorded during the observation period. Lower dose thalidomide effectiveness was evaluated by monitoring Hb level changes following dosage reduction.Results: The overall response rate (ORR) among the 48 participants was 91.7% (44 out of 48), with the main reaction (MaR) reaching 72.9% (35 out of 48). Hepatorenal toxicity was not monitored during the 2-year observation period, and there was no improvement in hemolysis. Most adverse effects were mild, with no instances of venous thrombosis and no cases of grade 2 or higher neurotoxicity. When the observation group was divided into three age categories (12- 14 years old, 14- 18 years old, and over 18 years old), there were no statistically significant differences in the occurrence of adverse reactions among the three groups. As there were some adverse reactions in ten cases, the treatment dose was reduced for them. The maintenance efficacy rate at one year of observation was 90% (9 out of 10).Conclusion: This study confirmed that thalidomide in small doses over a 2-year observation period is effective, and has no instances of grade 2 or higher neurotoxicity. Long-term maintenance with small doses is recommended for enhanced safety.Keywords: β-thalassemia, clinical efficacy, safety, thalidomide